Perancangan Maskot “Si Naryo” Untuk Program Sosial Kemasyarakatan Nasi Gratis Yogyakarta - Olivine Alifaprilina Supriadi; Dimas Krisna Aditya; Syarip Hidayat (JURNAL RUPA, 2022)
A mascot is a visual representative for a product, organization, and even social movements, and is made with the aim of carrying a certain message from the form it displays. The design of the mascot for the ‘Nasi Gratis Yogyakarta’ social movement is intended so that people, especially potential donors, are familiar with this program and are motivated to actively support the program. This research used qualitative method as data collecting method and design research. The design process started with data collection, determining the mascot concept, sketching, finishing, and revision. The design of the mascot ‘Si Naryo’ is expected to be an effective medium to introduce social programs and become an identity representative for the ‘Nasi Gratis Yogyakarta’. The results shows that the ‘Si Naryo’ mascot is quite effective because it is frequently used in every local event as the identity of the program, and started to get attention from the community. The existence of a mascot can give identity to a social activity, both as an identification that reflects the concept of the activity, as well as for commercial purposes. Keywordsmascot, visual identity, social movement